GE_GERICHTE P/17780/2023 vom 31. Januar 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;TENTATIVE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);MOTIVATION DE LA DÉCISION | Cst; CPP.3.al2; CPP.107; CPP.310; CP.181; CP.22